Estudio de sensibilidad de fenómenos transitorios en sistemas de redes abiertas por operación de dispositivos de control (2015)
In this document, a sensitivity analysis of the relations maximum dynamic pressure - static pressure (Pmax / P0) and minimum dynamic pressure - atmospheric pressure (Pmin / Patm) during the transient flow in an open network under pressure is presented. The study consisted of comparing the behavior of these variables adopting different flow rates, speed of the maneuver, types of valves, typologies, diameters and pipe lengths in networks with PVC pipes. As a main result of the analysis it is recommended to adopt closing times greater than or equal to 75T (150 L / a), in networks with PVC pipes, to guarantee that the maximum dynamic pressure does not exceed 20% of the static pressure nor the minimum dynamic pressure is less than atmospheric pressure. For the simulation of this phenomenon, the AFT Impulse® software was used and the closure of valves was used as the origin of the transient.